DISEMINASI INFORMASI PUBLIK MELALUI INSTAGRAM @kantahsikka PADA KANTOR PERTANAHAN KABUPATEN SIKKA - Lodowik Nikodemus Kedoh; Intan Mustafa; Veronika Melyana Novita; Viktor Ariestyan Sedu (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
The development of digital technology has encouraged government institutions to utilize social media as a public information dissemination tool to promote transparency, accountability, and public participation. This study aims to analyze public information dissemination through the Instagram account @kantahsikka managed by the Land Office of Sikka Regency, focusing on content types, information management mechanisms, user interaction, and its contribution to public information openness. This research employs a qualitative approach with a descriptive method. Data were collected through observation of Instagram posts, documentation of digital content, and in-depth interviews with account managers and related personnel. The findings indicate that Instagram @kantahsikka functions as a primary medium for disseminating public information on land services, including service information, official announcements, activity documentation, and land education content presented in visual formats. The dissemination mechanism follows a systematic process consisting of input, processing, and output stages; however, challenges remain in terms of posting consistency, thematic continuity, and responsiveness to public interactions. User engagement reflects a strong public demand for practical and service-oriented information. This study concludes that Instagram holds significant potential as a public information dissemination medium at the local government level, yet requires more structured and professional management to effectively enhance land service quality and public information transparency.